2016
DOI: 10.3390/nu8050288
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Pacing from Food or Supplementation Improves Physical Performance in Overweight Men and Women: The PRISE 2 Study

Abstract: We recently reported that protein-pacing (P; six meals/day @ 1.4 g/kg body weight (BW), three of which included whey protein (WP) supplementation) combined with a multi-mode fitness program consisting of resistance, interval sprint, stretching, and endurance exercise training (RISE) improves body composition in overweight individuals. The purpose of this study was to extend these findings and determine whether protein-pacing with only food protein (FP) is comparable to WP supplementation during RISE training o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Subjects were also provided all food and beverage intake, which added an extra layer of control and strengthened the findings. Augmenting this body of literature is Arciero et al’s work on “protein-pacing” (4–6 meals/day, >30% protein per meal resulting in >1.4 g/kg/d), which has demonstrated this method’s superiority over conventional, lower-protein/lower-frequency diets for improving body composition in hypocaloric conditions [ 81 , 82 ].…”
Section: Major Diet Archetypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects were also provided all food and beverage intake, which added an extra layer of control and strengthened the findings. Augmenting this body of literature is Arciero et al’s work on “protein-pacing” (4–6 meals/day, >30% protein per meal resulting in >1.4 g/kg/d), which has demonstrated this method’s superiority over conventional, lower-protein/lower-frequency diets for improving body composition in hypocaloric conditions [ 81 , 82 ].…”
Section: Major Diet Archetypesmentioning
confidence: 99%
“…However, the contrary has been demonstrated. Meal replacement products (powders, shakes, and bars) have matched or outperformed the effectiveness of whole food-based diets for weight loss and weight loss maintenance [ 82 , 122 , 123 ].…”
Section: Mechanisms Governing Changes In Body Composition Vis a Vis Dmentioning
confidence: 99%
“…Some studies support a pulse-feeding pattern in which a high protein meal might saturate the splanchnic sequestration leading to a higher availability of amino acids for muscle protein synthesis [ 12 , 13 ]. In contrast, several other studies reported an optimized muscle protein synthesis using a more continuous availability of amino acids in a spread-feeding pattern [ 14 , 15 , 16 , 17 , 18 ]. As yet, the current literature is not conclusive about the most efficient protein intake distribution for optimal muscle protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus if efficacious protein feedings are placed too close together it remains possible that the ability of skeletal muscle anabolism to be fully activated might be limited. While no clear consensus exists as to the acceptance of this theory, conflicting findings exist between longitudinal studies that did provide protein feedings in close proximity to each other [ 16 , 110 , 153 ], making this an area that requires more investigation. Finally, while the mechanistic implications of pulsed vs. bolus protein feedings and their effect on MPS rates may help ultimately guide application, the practical importance has yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%